Wills in Islamic Law - Alsalheen, Moftah (Al-Mukhtar Journal of Social Sciences, 2024)
Wills are significant issues in Islamic law that regulate individuals' rights in distributing their wealth after their death. This study aims to understand the concept of wills in Islamic law and its provisions regarding inheritance, beneficiaries, and the required conditions for a valid will. The study analyzes relevant legal texts and the different jurisprudential opinions of scholars in this context. It sheds light on the legal and ethical implications associated with the process of making a will and its impact on the Muslim society. This study contributes to increasing awareness and deepening understanding of wills in Islamic law, providing a legal and ethical framework for their proper and fair implementation.
Keywords: Wills; Islamic law; inheritance; rights; conditions